Mucosal immunity: its role in defense and allergy - Tlaskalová-Hogenová, Helena; Tucková, Ludmila; Lodinová-Zádniková, Rája; Stepánková, Renata; Cukrowska, Bozena; Funda, David P; Striz, Ilja; Kozáková, Hana; Trebichavský, Ilja; Sokol, Dan; Reháková, Zuzana; Sinkora, Jirí; et al. (International archives of allergy and immunology, 2002)
The interface between the organism and the outside world, which is the site of exchange of nutrients, export of products and waste components, must be selectively permeable and at the same time, it must constitute a barrier equipped with local defense mechanisms against environmental threats (e.g. invading pathogens). The boundaries with the environment (mucosal and skin surfaces) are therefore covered with special epithelial layers which support this barrier function. The immune system, associated with mucosal surfaces covering the largest area of the body (200-300 m(2)), evolved mechanisms discriminating between harmless antigens and commensal microorganisms and dangerous pathogens. The innate mucosal immune system, represented by epithelial and other mucosal cells and their products, is able to recognize the conserved pathogenic patterns on microbes by pattern recognition receptors such as Toll-like receptors, CD14 and others. As documented in experimental gnotobiotic models, highly protective colonization of mucosal surfaces by commensals has an important stimulatory effect on postnatal development of immune responses, metabolic processes (e.g. nutrition) and other host activities; these local and systemic immune responses are later replaced by inhibition, i.e. by induction of mucosal (oral) tolerance. Characteristic features of mucosal immunity distinguishing it from systemic immunity are: strongly developed mechanisms of innate defense, the existence of characteristic populations of unique types of lymphocytes, colonization of the mucosal and exocrine glands by cells originating from the mucosal organized tissues ('common mucosal system') and preferential induction of inhibition of the responses to nondangerous antigens (mucosal tolerance). Many chronic diseases, including allergy, may occur as a result of genetically based or environmentally induced changes in mechanisms regulating mucosal immunity and tolerance; this leads to impaired mucosal barrier function, disturbed exclusion and increased penetration of microbial, food or airborne antigens into the circulation and consequently to exaggerated and generalized immune responses to mucosally occurring antigens, allergens, superantigens and mitogens.
Keywords: sliznice; Immune Tolerance; Animals; Hypersensitivity; epitel; Humans; lidé; imunoterapie; Immunotherapy; zvířata; Immunity, Mucosal; slizniční imunita; Epithelium; imunologická tolerance; alergie; Mucous Membrane